Review and Progress towards the Capacity Boost of Overhead and Underground Medium-Voltage and Low-Voltage Broadband over Power Lines Networks: Cooperative Communications through Two- and Three-Hop Repeater Systems. (28th March 2013) - Lazaropoulos, Athanasios G.
Abstract : This paper reviews and analyzes the broadband capacity and the coexistence potential of overhead and underground medium-voltage/broadband over power lines (MV/BPL) and low-voltage/broadband over power lines (LV/BPL) topologies when one and two repeaters are additively deployed between their existing transmitting and receiving ends (overhead and underground MV/BPL and LV/BPL topologies with two- and three-hop repeater system, respectively). The contribution of this paper is four fold. First, the factors that influence the broadband capacity performance of overhead and underground MV/BPL and LV/BPL topologies with multihop repeater systems are identified, namely the number of repeaters, the distribution power grid type—either overhead or underground, either MV or LV, the initial distribution BPL topology, the multiconductor transmission line configuration, and coupling scheme applied. Second, the well-validated applicability of two-hop repeater systems is now extended in overhead and underground LV/BPL and MV/BPL networks. The significant mitigating role of two-hop repeater systems against capacity losses due to aggravated topologies or different coupling schemes is verified. Third, the deployment upgrade of two- to three-hop repeater systems in distribution BPL topologies is first examined in terms of broadband capacity performance. To study the occurred capacity improvement, suitable capacity contour plots are first proposed. Fourth, multi-hop repeater systems are identified as valuable technology solution so that the required intraoperability between overhead and underground MV/BPL and LV/BPL networks, which is a prerequisite condition before BPL systems symbiosis with other broadband technologies (interoperability), is promoted.